2019
DOI: 10.2989/16073606.2019.1686439
|View full text |Cite
|
Sign up to set email alerts
|

Fibonacci numbers which are concatenations of two repdigits

Abstract: We show that the only Fibonacci numbers that are concatenations of two repdigits are 13,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 9 publications
1
31
0
Order By: Relevance
“…. , α (k) for all roots of Ψ k (x) with the convention that α (1) := α. We now consider, for an integer k ≥ 2, the function…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…. , α (k) for all roots of Ψ k (x) with the convention that α (1) := α. We now consider, for an integer k ≥ 2, the function…”
Section: Preliminariesmentioning
confidence: 99%
“…Since then this result was generalised and extended in various directions. For example, in [1], we found all Fibonacci numbers which are concatenations of two rep-digits. In [14],…”
Section: Introductionmentioning
confidence: 99%
“…In [1], the authors considered Fibonnaci numbers which are concatenations of two repdigits (in base 10) and showed that the largest such number is F 14 = 377. Recently, diophantine equations involving Padovan numbers and repdigits have also been studied.…”
Section: (1)mentioning
confidence: 99%
“…A first result in this direction was proved, in 2000, by F. Luca [3] who showed that the largest Fibonacci number with only one distinct digit is F 10 = 55. After this, many authors worked on repdigits (i.e., integers having only one distinct digit in its decimal expansion) as expressions related to sum, product of terms of binary recurrences (see [4][5][6][7][8][9][10][11][12][13] and references therein). However, the related problem of finding all Fibonacci numbers with only two distinct digits remains open.…”
Section: Introductionmentioning
confidence: 99%